2018
DOI: 10.1007/s00204-018-2328-3
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of tissue factor induction by the uremic toxin indole-3 acetic acid through aryl hydrocarbon receptor/nuclear factor-kappa B signaling pathway in human endothelial cells

Abstract: Chronic kidney disease (CKD) is associated with high risk of thrombosis. Indole-3 acetic acid (IAA), an indolic uremic toxin, induces the expression of tissue factor (TF) in human umbilical vein endothelial cells (HUVEC) via the transcription factor aryl hydrocarbon receptor (AhR).This study aimed to understand the signaling pathways involved in AhR-mediated TF induction by IAA.We incubated human endothelial cells with IAA at 50µM, the maximal concentration found in patients with CKD. IAA induced TF expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 65 publications
1
60
0
2
Order By: Relevance
“…3 We and others have demonstrated that TF, the main initiator of the coagulation, is increased in the plasma of patients with CKD 8,35 and that it is overexpressed in endothelial cells and vascular smooth muscle cells in response to various tryptophan-derived uremic toxin (TDUT) in vitro. 6,8,10,36 Here we show the TF increases in the aorta and in the wall of renal vessels in both types of CKD mice. In addition, we also observed renal expression of TF in arterioles and peritubular capillaries in adenine-fed mice highlighting the role of local inflammation in TF induction for this model.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…3 We and others have demonstrated that TF, the main initiator of the coagulation, is increased in the plasma of patients with CKD 8,35 and that it is overexpressed in endothelial cells and vascular smooth muscle cells in response to various tryptophan-derived uremic toxin (TDUT) in vitro. 6,8,10,36 Here we show the TF increases in the aorta and in the wall of renal vessels in both types of CKD mice. In addition, we also observed renal expression of TF in arterioles and peritubular capillaries in adenine-fed mice highlighting the role of local inflammation in TF induction for this model.…”
Section: Discussionsupporting
confidence: 56%
“…These indolic compounds induce tissue factor (TF) in both the endothelial cells and vascular smooth muscle cells (vSMCs). 6,8,10,11 In CKD patients, the balance of pro-and antithrombotic factors in blood is altered. Indeed, several prothrombotic hemostatic mediators are elevated, including fibrinogen, soluble thrombomodulin, soluble TF, thrombin-antithrombin TAT complex, von Willebrand factor, Factor VIII, and C-reactive protein (CRP).…”
Section: Introductionmentioning
confidence: 99%
“…AhR protein expression was additionally positively associated with plasma levels of another indolic uremic toxin, indole-3 acetic acid (IAA) [88]. IAA is responsible for some adverse effects potentially related to the increased cardiovascular risk of CKD patients, such as increasing the expression of tissue factor in human vascular cells via the AhR [89]. However, up to now it is unknown to what extent the circadian expression of AhR is disrupted in CKD, what role might uremic toxins and the microbiota have in this phenomenon and what the consequences in any alterations in this system circadian regulation might be for CKD patients.…”
Section: Uremic Toxinsmentioning
confidence: 99%
“…Açaí fruits from the Amazon region (Belém do Pará, Brazil, 2 • 57 ′ 29,47 ″ S/47 • 23 ′ 10,37 ″ W) were processed to obtain the hydro-alcoholic extract as previously described (Rocha et al 2007 HUVECs preserve endothelial cell native characteristics, including the expression of specific surface markers and intracellular signalling pathways. HUVECs were chosen as an experimental model in this study, since they have been a useful model to investigate endothelial dysfunction promoted by uraemic toxins (Dou et al 2004(Dou et al , 2007Faure et al 2006;Gross et al 2015;Lu et al 2016;Migliori et al 2015) and also other biological actions (Addi et al 2019;Shen et al 2016).…”
Section: Açaí Seed Extractmentioning
confidence: 99%